2022
DOI: 10.1177/21677026211059524
|View full text |Cite
|
Sign up to set email alerts
|

Which Anxious Adolescents Were Most Affected by the COVID-19 Pandemic?

Abstract: Although the COVID-19 pandemic caused significant stress and anxiety among many people, individuals’ experiences varied. We examined whether specific forms of anxiety predicted distinct trajectories of anxiety, perceived stress, and COVID-related worries during 3 early months of the pandemic. In a longitudinal study ( N = 291), adolescents’ ( n = 194) social anxiety and generalized anxiety levels were assessed via parent reports and self-reports and clinical diagnostic interviews. Later, when these adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 54 publications
(77 reference statements)
1
10
0
Order By: Relevance
“…Several studies have confirmed that these baseline levels were a strong risk factor for mental health difficulties during the pandemic ( Czeisler et al, 2020 ; McGinty et al, 2020 ; Fancourt et al, 2021 ; Shanahan et al, 2022 ). For instance, people who reported higher levels of anxiety even before the pandemic experienced a steeper decline in mental health during the pandemic (e.g., Morales et al, 2022 ). Even though we do not have the pre-pandemic data, our results suggest that general/mental health is a significant predictor of COVID anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed that these baseline levels were a strong risk factor for mental health difficulties during the pandemic ( Czeisler et al, 2020 ; McGinty et al, 2020 ; Fancourt et al, 2021 ; Shanahan et al, 2022 ). For instance, people who reported higher levels of anxiety even before the pandemic experienced a steeper decline in mental health during the pandemic (e.g., Morales et al, 2022 ). Even though we do not have the pre-pandemic data, our results suggest that general/mental health is a significant predictor of COVID anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…The scale was preceded by a brief text explaining what a stressful event is and that the health emergency due to COVID-19 can be defined as a stressful event. Thus, the students were asked to respond to the items on how they felt in the last month, referring to COVID-19 (e.g., Morales et al, 2022). After reverse scoring answers to the positive items, a total PSS-10 score was computed by averaging across the 10 items so that higher scores reflected higher levels of stress.…”
Section: Methodsmentioning
confidence: 99%
“…Participants responded to each item using a 5-point Likert scale ranging from 1 (very little or not at all) to 5 (a great deal), with higher scores reflecting greater concern. As a composite score, recent research using this scale indicates good test-retest reliability (rs > .73) and good internal consistency (α = .80-.88; Kuhlman et al, 2021;Morales et al, 2022).…”
Section: Covid-19-related Concernsmentioning
confidence: 99%